Cortical pathology in multiple sclerosis patients with epilepsy: a 3 year longitudinal study. Issue 1 (2nd September 2011) - Calabrese, M; Grossi, P; Favaretto, A; Romualdi, C; Atzori, M; Rinaldi, F; Perini, P; Saladini, M; Gallo, P
Abstract : Introduction: The cause of epilepsy in multiple sclerosis (MS) has not yet been elucidated. The relevance of cortical pathology (cortical lesions and thickness) in MS patients with and without epilepsy was evaluated in a longitudinal study. Methods: 32 relapsing–remitting MS patients with epilepsy (RRMS/E) and 60 matched RRMS patients without epilepsy were included in a 3 year longitudinal study. The following clinical and MR parameters were analysed: Expanded Disability Status Scale (EDSS), cognitive score (CS), cortical lesion (CL) number and volume, grey matter fraction (GMf), global cortical thickness (CTh), T2 white matter lesion volume (T2WMLV), new CLs and new WM lesions. Results: At baseline (T0), CLs were observed in 27/32 (84.4%) RRMS/E and in 26/60 (43.3%) RRMS (p<0.001) patients, and the RRMS/E group had a higher number (10.2±8.9 vs 4.5±2.4; p<0.001) and total volume (2.0±1.3 vs 0.7±0.8 cm 3 ; p<0.001) of CLs compared with the RRMS group. No significant difference in T2WMLV was observed. Global CTh was lower in RRMS/E (2.12±0.19 vs 2.35±0.14 mm; p<0.001), and this group also showed a decline in cognition (CS 10.9±6.3 vs 6.2±3.5; p<0.001). After 3 years (T1), the RRMS/E group had a higher accumulation of new CLs (3.4±3.2 vs 1.2±1.1; p<0.001) and faster reduction of GMf (p=0.022) while the two groups did not differ in the number of new WM and new Gad+ lesions. Discussion: RRMS/E had a more severe and rapidly evolving cortical pathology (CLs and atrophy) compared with RRMS without epilepsy. The RRMS/E group was also characterised by more pronounced cognitive decline, higher EDSS and higher prevalence of men.